2020
DOI: 10.1371/journal.pone.0233231
|View full text |Cite
|
Sign up to set email alerts
|

Small heat shock proteins determine synapse number and neuronal activity during development

Abstract: Environmental changes cause stress, Reactive Oxygen Species and unfolded protein accumulation which hamper synaptic activity and trigger cell death. Heat shock proteins (HSPs) assist protein refolding to maintain proteostasis and cellular integrity. Mechanisms regulating the activity of HSPs include transcription factors and posttranslational modifications that ensure a rapid response. HSPs preserve synaptic function in the nervous system upon environmental insults or pathological factors and contribute to the… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
12
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(15 citation statements)
references
References 53 publications
2
12
0
1
Order By: Relevance
“…Genetic modifications that affect the expression of sHsp23 or sHsp26, provokes an imbalance in chaperones equilibrium that causes a reduction in synapse number, reinforcing the idea of chaperone complex and protein quality system equilibrium. Thus, sHSPs in neurons participate in synapse maintenance and modulation of neuronal function (Santana et al, 2020).…”
Section: Hsps In Synaptic Maintenancementioning
confidence: 99%
See 1 more Smart Citation
“…Genetic modifications that affect the expression of sHsp23 or sHsp26, provokes an imbalance in chaperones equilibrium that causes a reduction in synapse number, reinforcing the idea of chaperone complex and protein quality system equilibrium. Thus, sHSPs in neurons participate in synapse maintenance and modulation of neuronal function (Santana et al, 2020).…”
Section: Hsps In Synaptic Maintenancementioning
confidence: 99%
“…Thus, the phosphorylation state can alter protein activity and interactions with chaperones clients as a key-mechanism to sHSPs regulation. In our recent work, we propose that that sHSP23 and 26 neuronal functions are mediated by a novel putative kinase protein CG1561, named Pinkman (Pkm) (Santana et al, 2020).…”
Section: Shsps Balance In Synapse Maintenancementioning
confidence: 99%
“…Chaperones contribute a great deal to cytoskeletal stability, which is especially important for neurons to sustain their complex processes ( Table 2; Bakthisaran et al, 2015;Nefedova et al, 2015;Nefedova et al, 2017;Kelliher et al, 2019;Muranova et al, 2019;Vallin and Grantham, 2019;Muranova et al, 2020). Many chaperones are implicated specifically in axonal morphology: manipulation of several small heat shock proteins as well as Hsp70 and 90 was found to significantly decrease synapse number in Drosophila neuromuscular junctions (Santana et al, 2020), and an Hsp70 orthologue has been found to assist in polarized trafficking of synaptic vesicle proteins to axons (Fukuzono et al, 2016).…”
Section: Protein Maintenance In Dendritic Arborizationmentioning
confidence: 99%
“…The interaction of chaperones may be the key to regulation of neuronal processes. Hspb6 has been found to act as a modulator of activity for other small Hsps in human cell culture (Weeks et al, 2018;Mymrikov et al, 2020;Santana et al, 2020). Furthermore, individual overexpression of Hsp23 or Hsp26 led to decreased number of synapses in the Drosophila neuromuscular junction, but combined overexpression of Hsp23 and Hsp26 together resulted in an increase in synapse numbers.…”
Section: Protein Maintenance In Cell-type Specificitymentioning
confidence: 99%
See 1 more Smart Citation